2021
DOI: 10.1051/e3sconf/202132401002
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics abundance in gills and gastrointestinal tract of Epinephelus fuscoguttatus-lanceolatus at the Coastal of Pulau Panjang, Serang, Banten

Abstract: Microplastics are plastic particles in the size of <5 mm. Bioaccumulation of microplastics in the marine biotas, including fishes, occurs through the food chain. Microplastics enter the fish body through their gills and mouth. Contamination of microplastics inside the fish body can cause several effects, such as increasing toxicity effect, and growth inhibition. This research analyzed the form and amount of the microplastics found in each gill and gastrointestinal tract of the fish samples. A total of 15 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Microplastics in body fish could enter through the digestive system and respiratory systems [10], either directly or indirectly. Plastic particles are ingested immediately when fish cannot distinguish between plastic and their prey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microplastics in body fish could enter through the digestive system and respiratory systems [10], either directly or indirectly. Plastic particles are ingested immediately when fish cannot distinguish between plastic and their prey.…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted on the gills, stomach, and intestines because previous research showed that microplastic content was found in these organs. Fish cannot avoid the presence of microplastics in water, so microplastics attach to the gills through absorption [10]. Most of the fish found in the gills and digestive tract contain fiber-type microplastics with a size >1000 µm [11].…”
Section: Introductionmentioning
confidence: 99%